2014
DOI: 10.1111/jpn.12175
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of tropical forages with exogenous fibrolytic enzymes: effects on chemical composition and in vitro rumen fermentation

Abstract: The effects of three treatments of fibrolytic enzymes (cellulase from Trichoderma longibrachiatum (CEL), xylanase from rumen micro-organisms (XYL) and a 1:1 mixture of CEL and XYL (MIX) on the in vitro fermentation of two samples of Pennisetum clandestinum (P1 and P2), two samples of Dichanthium aristatum (D1 and D2) and one sample of each Acacia decurrens and Acacia mangium (A1 and A2) were investigated. The first experiment compared the effects of two methods of applying the enzymes to forages, either at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
4
7
0
Order By: Relevance
“…5,000 µl) of FEE, which was certainly due to the higher TDOM and DNDF observed for these samples, in accordance with the findings of Soltan et al (2013) and Dineshkumar et al (2014). Previous studies suggested that fibrolytic enzymes may weaken and/or degrade the plant cell wall constituents thus facilitating the microbial attachment and enhancing ruminal fermentation (Díaz et al, 2015;Elghandour et al, 2016). Our study showed that the most elevated dose levels of FEE improved TDOM and DNDF of different tropical forages and this could be a result of the higher substrate hydrolysis and synergism with other ruminal enzymes (Beauchemin et al, 2003;Elghandour et al, 2016;Eun & Beauchemin, 2008;López et al, 2016).…”
Section: Ta B L E 4 Pearson Correlation Coefficient For In Vitro Gas supporting
confidence: 89%
See 3 more Smart Citations
“…5,000 µl) of FEE, which was certainly due to the higher TDOM and DNDF observed for these samples, in accordance with the findings of Soltan et al (2013) and Dineshkumar et al (2014). Previous studies suggested that fibrolytic enzymes may weaken and/or degrade the plant cell wall constituents thus facilitating the microbial attachment and enhancing ruminal fermentation (Díaz et al, 2015;Elghandour et al, 2016). Our study showed that the most elevated dose levels of FEE improved TDOM and DNDF of different tropical forages and this could be a result of the higher substrate hydrolysis and synergism with other ruminal enzymes (Beauchemin et al, 2003;Elghandour et al, 2016;Eun & Beauchemin, 2008;López et al, 2016).…”
Section: Ta B L E 4 Pearson Correlation Coefficient For In Vitro Gas supporting
confidence: 89%
“…Elghandour et al (2016) observed some changes in SCFA profile with the addition of fibrolytic enzymes, but this variation was roughage dependent. The increase in propionate production suggests a change in the fermentation pattern, which affected C2:C3 ratio and this could be attributed to fermentation of soluble carbohydrates arising from cell wall degradation (Díaz et al, 2015;Romero et al, 2015) and also from the FEE (soluble carbohydrates). The improvement of C2:C3 ratio is an indication of better efficiency of energy utilisation in the rumen (Arriola et al, 2011).…”
Section: Studies Using Cellulase and Xylanase Enzymes Demonstrated Thatmentioning
confidence: 99%
See 2 more Smart Citations
“…is a forage plant of important use in livestock feeding, both for its great dry mass production and for its longevity and nutritive value (DIEHL et al, 2013). However, like most tropical forages, it has low nutritional value when harvested at an advanced stage of maturity, and as forage is the main component of ruminant diets in Brazil, the low-quality forage might result in low animal productivity (DÍAZ et al, 2015).…”
Section: Introductionmentioning
confidence: 99%